Exploring the Effectiveness of Cognitive Behavioral Therapy (CBT) in Reducing Anxiety and Depression Among Adolescents: A Counseling Approach - Alifa Suri Rahmadhina Rahmadhina; Betsi Siti Nurhidayah (Asesment : Journal Of Counseling Guidance, 2025)
Background: Anxiety and depression are prevalent mental health challenges among adolescents, significantly affecting their academic performance, social relationships, and overall well-being. While Cognitive Behavioral Therapy (CBT) is an established evidence-based intervention, its effectiveness in adolescent counseling contexts requires further evaluation.Objective: This study aims to evaluate the effectiveness of CBT in reducing anxiety and depression symptoms among adolescents aged 12–18 years, focusing on therapeutic mechanisms, implementation modalities, and practical applications within diverse counseling contexts.Method: A systematic literature review was conducted, analyzing 23 empirical studies published between 2019 and 2025. The review examined various CBT modalities, including individual therapy, group counseling, school-based interventions, and digital platforms, evaluating methodological quality, intervention characteristics, and outcome measures.Findings and Implications: CBT demonstrated moderate to large effect sizes in reducing anxiety (Cohen's d = 0.65–0.89) and depression symptoms (Cohen's d = 0.52–0.78) among adolescents. School-based programs and digital platforms showed comparable effectiveness to traditional face-to-face therapies while offering enhanced scalability and accessibility. The findings emphasize the need for age-appropriate modifications, family involvement, and cultural adaptation in CBT implementation.Conclusion: CBT represents an effective intervention for addressing anxiety and depression in adolescents across various delivery modalities. Successful implementation requires tailored approaches considering developmental characteristics, cultural contexts, and family dynamics. Further research is needed to explore long-term treatment effects, personalized approaches, and optimal combinations of therapeutic components for diverse adolescent populations.